A Mobile App for Promoting Breastfeeding-Friendly Communities in Hong Kong: Design and Development Study - Heidi Sze Lok Fan; Emily Tsz Yan Leung; Ka Wing Lau; Janet Yuen Ha Wong; Edmond Pui Hang Choi; Christine Lam; Marie Tarrant; Hextan Yuen Sheung Ngan; Patrick Ip; Chia Chin Lin; Kris Yuet Wan Lok (JMIR Formative Research)
Abstract BackgroundBreastfeeding is vital for the health and well-being of both mothers and infants, and it is crucial to create supportive environments that promote and maintain breastfeeding practices. ObjectiveThe objective of this paper was to describe the development of a breastfeeding-friendly app called “bfGPS” (HKU TALIC), which provides comprehensive territory-wide information on breastfeeding facilities in Hong Kong, with the goal of fostering a breastfeeding-friendly community. MethodsThe development of bfGPS can be categorized into three phases, which are (1) planning, prototype development, and preimplementation evaluation; (2) implementation and updates; and (3) usability evaluation. In phase 1, a meeting was held with experts, including maternal and child health researchers, app developers, breastfeeding individuals, and health professionals, to discuss the focus and functionality of the breastfeeding app. A prototype was developed, and breastfeeding facilities in various public venues in Hong Kong were assessed using a structured checklist. For the preimplementation evaluation, 10 focus groups and 19 one-on-one interviews were conducted between May 2019 and October 2020 with staff working in public premises (n=29) and breastfeeding individuals (n=29). For phase 2, bfGPS was published on iOS (Apple Inc) and Android (Google) platforms in September 2020. App updates were launched in September 2021 and May 2022 based on the suggestions provided by the participants in the preimplementation evaluation. For the usability evaluation, semistructured, in-depth, one-to-one interviews were conducted with breastfeeding individuals (n=30) to understand their experiences of using bfGPS. Content analysis was used to analyze the data. ResultsbfGPS is a mobile app that was developed to assist breastfeeding individuals in locating breastfeeding facilities in public venues in Hong Kong. In the preimplementation evaluation, the participants gave comments on the layout and interface of bfGPS, and suggestions were given on incorporating new functions into the app. Based on the suggestions of the participants in the preimplementation evaluation, a few additional functions were added into bfGPS, including allowing the users to rate and upload recent information about breastfeeding facilities and an infant tracker function that encourages users to record infant development. In the usability evaluation, 3 main themes emerged—bfGPS improves the community experience for breastfeeding individuals, facilitates tracking the infant’s growth, and provides suggestions for further development. ConclusionsThe bfGPS app is the first user-friendly tool designed to assist users in locating breastfeeding facilities within the community. It stands as a guide for similar health care app developments, emphasizing the importance of accurate, current data to ensure user adoption and long-term use. The app’s potential lies in the support and reinforcement of breastfeeding practices coupled with self-management strategies.